Analysis of predominant intensity of physical load in basketball players of different ages during competition and training - Balciunas, M.; Stonkus, S. (2003)
The correlation between the competitive (absolute) and training (relative) intensity of physical load (expressed in heart rate) is an important indicator of the basketball player`s training efficiency [1-3]. The aim of this research is to establish and assess the predominant intensity of load in basketball players of different ages during basketball competition and training. 11-12 (n = 30), 15-16 (n = 30) year-old basketball players from Kaunas basketball schools and 17-18 (n = 20) year-old players from LAPE and LAPE "Zalgiris" were examined and the load intensity was established during competitions and trainings. The main conclusion was that physical loads were not equivalent during training and competition in players with different functions and of different ages.